Measurement of Glutathione as a Tool for Oxidative Stress Studies by High Performance Liquid Chromatography - Nuhu, Faisal; Gordon, Andrew; Sturmey, Roger; Seymour, Anne Marie; Bhandari, Sunil (Molecules, 2020)
Background: Maintenance of the ratio of glutathione in the reduced (GSH) and oxidised (GSSG) state in cells is important in redox control, signal transduction and gene regulation, factors that are altered in many diseases. The accurate and reliable determination of GSH and GSSG simultaneously is a useful tool for oxidative stress determination. Measurement is limited primarily to the underestimation of GSH and overestimation GSSG as a result of auto-oxidation of GSH. The aim of this study was to overcome this limitation and develop, optimise and validate a reverse-phase high performance liquid chromatographic (HPLC) assay of GSH and GSSG for the determination of oxidant status in cardiac and chronic kidney diseases. Methods: Fluorescence detection of the derivative, glutathione-O-pthaldialdehyde (OPA) adduct was used. The assay was validated by measuring the stability of glutathione and glutathione-OPA adduct under conditions that could affect the reproducibility including reaction time and temperature. Linearity, concentration range, limit of detection (LOD), limit of quantification (LOQ), recovery and extraction efficiency and selectivity of the method were assessed. Results: There was excellent linearity for GSH (r2 = 0.998) and GSSG (r2 = 0.996) over concentration ranges of 0.1 μM–4 mM and 0.2 μM–0.4 mM respectively. The extraction of GSH from tissues was consistent and precise. The limit of detection for GSH and GSSG were 0.34 μM and 0.26 μM respectively whilst their limits of quantification were 1.14 μM and 0.88 μM respectively. Conclusion: These data validate a method for the simultaneous measurement of GSH and GSSG in samples extracted from biological tissues and offer a simple determination of redox status in clinical samples.
Keywords: Glutathione analysis; Oxidative stress; HPLC; GSH; GSSG